A Comparative Study of Learning Behaviour of Students of Public and Private Universities in Islamabad - Yaqoob, Maria; Mirza, Faria Ibad (Pakistan Journal of Humanities and Social Sciences, 2025)
Education is now universally recognized to be the prime key to the moral, cultural, political, and socio-economic development of a nation. Every individual has a variety of behaviors, which might be positive or negative, and can vary according to their favorability and unfavorability for various attitudinal objects. The main objectives of the study was to find out learning behaviors, teacher-student relationships, classroom environments, and compare educational quality among students of selected public and private universities in Islamabad, Pakistan. A quantitative, descriptive, and comparative methodology was utilized. A total of 250 students (125 from public schools and 125 from private schools) filled out a 47-item questionnaire in person between June and July 2019. The questions were divided into four categories: learning behavior, teacher-student interaction, classroom environment, and quality of education. The value of Cronbach's alpha for each subscale ranged from 0.69 to 0.88, indicating the instrument's reliability. According to the findings, the students of private universities reported higher levels of educational quality, more supportive teacher-student relationships, better classroom environments, and more positive learning behavior compared to public universities. In the light of constructivist interpretation, the results show that teacher support, institutional resources, and interactive environments all contribute to better learning outcomes. This paper includes a discussion of the real-world significance of teaching methods and higher education policy.